STUDI AKTIVITAS MASJID KAMPUS DAN PEMBINAAN IMAN DAN TAQWA BAGI MAHASISWA DI PERGURUAN TINGGI UMUM (Studi ke Arah Perumusan Standardisasi Masjid Kampus dan Model Bina IMTAQ di PTU JABAR) - Cecep Alba (Fakultas Seni Rupa dan Desain ITB, 2011)
Campus mosque, as other mosques at the center of society, considered strategic in the creation of the religious atmosphere on campus. Campus mosque is not only as a center for ritual worship but also as a place of student activities. The mosque is a resource center, where the collection and distribution of zakat, the cadre and the development of Islamic religious knowledge take a place. The focus of this research is how the mosque campus activities and student religious activity, as well as how well the leadership expectations of PTU, DKM Masjid Campus administrators, students, PTU, and PTU lecturer PAI are against the activities of mosques and religious activities campus student. In particular, this study aims to determine the profile of the campus mosque, the mosque management campuses in Indonesia, the activity of the campus mosque, the substance of the material that is taught in PAI in the mosque and and the PTU, the number of credits of courses provided and PAI lecture method in PTU Jabar. The most relevant method in the study is descriptive-analytic, namely a study trying to uncover the problem is going to be described, analyzed, concluded and recommended to determine a policy. With this method the data are obtained and analyzed quantitatively and qualitatively. Research includes preparation of the TOR (Term of Reference), research instruments, testing the validity of the contents of the instrument, collect data, verify data, process the data, drafting of research reports, seminars, research, revision of research reports, research reports as well as doubling the research report.